2015
DOI: 10.1016/j.seizure.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria currently proposed for “ictal epileptic headache”: Perspectives on strengths, weaknesses and pitfalls

Abstract: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 25 publications
(68 reference statements)
7
39
0
Order By: Relevance
“…We agree with Hartl et al that recognition of visual aura as an epileptic manifestation per se still represents a challenge because of occipital lobe epilepsy may be neglected in patients with migraine as well as headache as the sole clinical manifestation of an epileptic seizure . Noteworthy, the patients reported by Hartl et al suffered symptomatic occipital epilepsy due to gliosis (patient 1) and an arterio‐venous malformation (AVM) (patient 2).…”
supporting
confidence: 86%
“…We agree with Hartl et al that recognition of visual aura as an epileptic manifestation per se still represents a challenge because of occipital lobe epilepsy may be neglected in patients with migraine as well as headache as the sole clinical manifestation of an epileptic seizure . Noteworthy, the patients reported by Hartl et al suffered symptomatic occipital epilepsy due to gliosis (patient 1) and an arterio‐venous malformation (AVM) (patient 2).…”
supporting
confidence: 86%
“…This bears resemblance to “ictal epileptic headache” observed especially in the pediatric age group diagnosis of painful seizures which is based on similar grounds [4].…”
Section: Discussionsupporting
confidence: 56%
“…According to this, ictal epileptic headache is a condition in which a headache lasting from minutes to days is the sole manifestation of an epileptic seizure. In addition, an EEG demonstration of epileptiform discharges as well as improvement of headache following AED administration, are required [26][27][28]. It has been suggested that the migralepsy concept might actually not exist at all and that it represents an epileptic event that starts with an ictal epileptic headache followed by other epileptic symptoms [29,30].…”
Section: Discussionmentioning
confidence: 99%